Donde no estén ustedes. Prism of the Narrative of Horacio Castellanos Moya - González Sánchez, Esteban (2018)
This article describes Donde no estén ustedes in the context of the narrative of Horacio Castellanos Moya. In this text two narrative processes converge: one of the tragic history of the Aragón-Baldonini family and the other of detective series. Interpretative readings are proposed to show the relationship between the reason for the descent and visit to hell within the structure of the new detective novel.